Template-Free Synthesis of One-Dimensional g-C3N4 Chain Nanostructures for Efficient Photocatalytic Hydrogen Evolution - Zhang, Mingyi; Sun, Ye; Chang, Xin; Zhang, Peng (Frontiers in Chemistry, 2021)
The development of graphite-carbon nitride (g-C3N4) photocatalyst is of great significance for various visible utilization applications. Control the nanostructures of g-C3N4 can tailor its photocatalytic performance. In this paper, one-dimensional chain-like g-C3N4 was successfully synthesized by heat-induced polymerization of melamine which was saturated in ethylene glycol. The photocatalytic hydrogen production rate (HER) of the prepared g-C3N4 chain enhanced about 3 times than that of bulk g-C3N4, increasing from 9.6 μmolh−1 to 28.7 μmolh−1. The improved photocatalytic activity of the g-C3N4 chain was attributed to the advantages of porosity and nanostructure. The extraordinary nanopores result in an enlarged specific surface area for adsorption and the production of abundantly available channels for charge transfer. The one-dimensional chain-like structure can facilitate the exposure of internal/external active sites as many as possible, and induce the directional migration of charge carriers.